Post-weld heat treatment effects on hardness and impact strength of aluminum alloy 6061 friction stir Butt weld - Jitlada Boonma (2018)
© 2015 The Japan Institute of Metals and Materials. Butt joint friction stir welding (FSW) of aluminum alloy 6061-T651 rolled plate was prepared and the weld specimens were post weld heat treated (PWHT) by solution heat treatment and aging. The hardness, toughness and fracture surface of the PWHT and as-welded specimens were investigated and their relationships were discussed. The effects of FSW are found to soften the nugget zone and thermomechanical affected zone in the as-welded condition, however, the PWHT can provide a full strength recovery in the whole weld specimen. Results from the analysis of relationship of the hardness-tensile strength found that the tensile strength (TS) is linearly proportional to the Vickers hardness number (VHN) with a TS to VHN ratio of about 2.75. However, the linear proportion with a negative slope of the hardness-toughness relationship is observed with the characteristic toughness constant of about 40 J for AA 6061. From fracture surface investigation, the unique fracture characteristics comprising double V grooves and double sharp hills with strips equivalent to the cup and cone fracture of the tensile fracture of medium ductile alloys are observed.